2000
DOI: 10.1590/s1516-44462000000200004
|View full text |Cite
|
Sign up to set email alerts
|

Nortriptyline blood levels and clinical outcome: meta-analysis of published studies

Abstract: INTRODUCTION: An optimum range has been suggested for nortriptyline blood levels, above or below which patients respond poorly or do not respond at all to treatment. METHODS: A meta-analysis of published studies was performed to verify the existence of an optimal blood concentration range or therapeutic window in nortriptyline-treated depression patients. A MEDLINE search through the years 1970-1999 was carried out to identify original papers and review articles. Data concerning blood levels and percentage imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…1 Nicotine increases phosphorylation of CREB (P-CREB) in the ventral tegmental area, 1 while nicotine withdrawal decreases P-CREB. 2 Nicotine-induced P-CREB increase is absent in MOR À/À knockout (KO) mice and is also blocked by the MOR antagonist naloxone in wild-type mice. 1 The MOR promoter has a cAMPresponsive element that binds P-CREB, which is thought to drive expression of MOR.…”
Section: Mgmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Nicotine increases phosphorylation of CREB (P-CREB) in the ventral tegmental area, 1 while nicotine withdrawal decreases P-CREB. 2 Nicotine-induced P-CREB increase is absent in MOR À/À knockout (KO) mice and is also blocked by the MOR antagonist naloxone in wild-type mice. 1 The MOR promoter has a cAMPresponsive element that binds P-CREB, which is thought to drive expression of MOR.…”
Section: Mgmentioning
confidence: 99%
“…1,2 Our group has demonstrated that there is a biphasic curvilinear relationship between plasma levels of nortriptyline and behavior, using the tail suspension test, 3 an animal model employed to screen for drugs with antidepressant effects. Although noradrenergic drugs are known to induce c-Fos expression in central neurons, only one study has investigated the effects of nortriptyline on the expression of brain c-Fos.…”
mentioning
confidence: 99%